AUTO SOLDERING: AUTOMATION OF THE SOLDERING PROCESS FOR TRANSFORMER COIL TERMINALS - Damasceno, Alexandre Holanda; Bruno, Léo Fernando Castelhano; de Lima, Maria de Lourdes Santos; dos Santos, Victor Abreu; Natário, Luis Felipe Trindade (Seven Editora, 2026)
This article describes the development of the AUTO SOLDERING project, the result of an PD&I initiative conceived and executed by B&Z International in the industrial context, with its scientific production coordinated by IITA. The project is aimed at the design and implementation of an automated tin immersion soldering system applied to transformer coil terminals used in cell phone chargers. The initiative stems from the need to replace the manual and semi-automatic process currently employed, which exposes operators to health and safety risks and presents instabilities regarding repeatability, reproducibility and control of critical parameters. The proposed solution is based on an integrated hardware and software prototype capable of automating the stages of insertion, handling, fluxing, immersion soldering and transfer of the product to the subsequent stage. The system includes control of essential variables (time, depth and immersion angle) and continuous monitoring of temperature, weld volume and cycle time. As a differential, it uses embedded intelligence for real-time decision-making, aiming at operational stability and quality standardization. Additionally, it allows the collection and availability of productive data for integration into the CMES system through XML files, supporting performance indicators and traceability. The development considers ergonomics, occupational safety and compliance with NR-12. As expected results, the elimination of operator exposure to the process, increased efficiency and availability, improved quality and greater control of production indicators stand out, characterizing incremental process innovation applied to the industrial context.